Pengelolaan Limbah Pasar Organik Menjadi Produk Eco Enzyme Dalam Upaya Mengurangi Pencemaran Lingkungan - Meilinda Suriani Harefa; Syukri Hidayat; Ema Serika Br. Ginting; Queen Helen Br. Bukit; Nadratul Aini Lubis (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Trash is often found in public places, and traditional markets are one of the public places where a large amount of trash is generated. Market activities generate a large amount of waste, including unused and unwanted leftovers from market stalls and stalls.One step towards reducing the amount of organic waste on the market is the production of eco-enzymes. This can be done through various methods such as aerobic or anaerobic composting and the production of eco-enzymes.This eco-enzyme production is an efficient solution in terms of space management and can also be used in home environments.